Enhanced Localized Electric Field from Surface Plasmon Coupling in a Silver Nanostructure Array with a Silver Thin Film for Bioimaging and Biosensing - Kota Yamasaki; Ryohei Hatsuoka; Kenji Wada; Tetsuya Matsuyama; Koichi Okamoto (Photonics)
The electric field enhancement effect induced by localized surface plasmon resonance (LSPR) plays a critical role in imaging and sensing applications. In particular, nanocube structures with narrow gaps provide large hotspot areas, making them highly promising for high-sensitivity applications. This study predicts the electric field enhancement effect of structures combining silver nanocubes and a 10 nm thick silver thin film using the finite-difference time-domain (FDTD) method. We demonstrate that the interaction between the silver nanocubes and silver thin film allows control over sharp LSPR peaks in the visible wavelength range. Specifically, the structure with a spacer layer between the silver nanocubes and the silver thin film is suitable for multimodal imaging, while the direct contact structure of the silver nanocubes and the silver thin film shows potential as a highly sensitive refractive index sensor. The 10 nm thick silver thin film enables backside illumination due to its transparency in the visible wavelength region, making it compatible with inverted microscopes and allowing for versatile applications, such as living cell imaging and observations in liquid media. These structures are particularly expected to contribute to advancements in bioimaging and biosensing.